(untitled) (Texas Journal of Engineering and Technology, 2023)
One factor that affects the quality of the threads collected in modified ring collection mode is the vyurok speed. To determine the speed of the alternative vyurok, the ratio of the vyurok speed to the speed of the ringed assembly machine has been studied. Speed ratio is 0.99; When it was 0.89 and 0.81, the quality of the threads collected was compared comparatively. According to the results, the quality indicators of the threads collected at a speed of 0.89 were found to be good